Genetic effects of double muscle and slick hair mutations on selection criteria and genomic study for water efficiency in senepol cattle - Souza, Christhian Borges de (2024)
Concerns about climate change, water resources, and scarcity encourage new research and solutions in all industry sectors, and the livestock is no exception. The possibility of practicing genetic selection to reduce the water footprint of beef may be a viable alternative. However, the inclusion of new traits in breeding programs requires a prior study of their impact on already established traits such as weight gain. Thus, the aim of this study was to describe the genetic parameters of water efficiency measures and conduct a Genome-Wide Association Study (GWAS), as well as Post-GWAS, to assess the effect of Double Muscle (DM) and Slick Hair mutations on selection criteria. Data were provided by the Brazilian Association of Senepol Cattle Breeders - ABCB Senepol and the Embrapa Geneplus Program. It was observed that individuals carrying Slick Hair and not carrying DM are the most recommended. Heritability averages were found for water efficiency measures, and the phenotypic correlation values between weight gain and residual water intake were null. In addition, showed a genetic association of medium to high magnitude with residual feed intake, making them more attractive for selection. This is different from gross measurements that demonstrate a medium to high genetic association with weight gain. Water intake and dry matter intake demonstrated high genetic association (0.85). Only for water conversion ratio were significant SNPs found, reinforcing the polygenic nature of these traits. Enrichment analyses revealed that various biological processes are involved in the expression of this phenotype. In general, there is genetic variability for water efficiency selection; these traits demonstrate a polygenic nature, and several biological processes linked to saliva production, heat stress, water transport, imune sistem, lipid metabolism and oxidoreductase activity are involved with phenotype. Keywords: Adapted Taurine. Genetic Parameters. Genome Wide Association Study. Post-GWAS.